Characteristics of psychological time in patients with depression and potential intervention strategies - Ren, Hanlin; Zhang, Qing; Ren, Yanzhen; Zhou, Qiang; Fang, Yuan; Huang, Liang; Li, Xiaobao (Frontiers in Psychiatry, 2023)
Psychological time reveals information about an individual’s psychological state and psychopathological traits and, thus, has become a new perspective through which the occurrence and development of depression can be examined. Psychological time includes time perception, time perspective, circadian rhythms, and passage of time. Patients with depression are characterized by inaccurate time interval estimation, habitual negative thoughts about the past and future, evening-type circadian rhythms, and slow passage of time. Habitual negative thoughts about the past and future and evening-type circadian rhythms influence the formation of depression, and poor time interval estimation and slow passage of time may result from depression. Further study is needed accurately exploring psychological time and influencing factors in patients with depression, and prospective cohort studies could further clarify this complex relationship. In addition, the study of psychological time has important implications for developing effective interventions to reduce depression.